2021
DOI: 10.1029/2020ja028891
|View full text |Cite
|
Sign up to set email alerts
|

On the Association Between Electron Flux Oscillations and Local Phase Space Density Gradients

Abstract: Electron flux oscillations are often observed in electron energy channels in the range of 10 keV to 100 keV. They are observed in the form of flux fluctuations with periods corresponding to the drift periods of electrons around the Earth and can be produced in the magnetosphere as a result of drift resonant interactions in association with broadband ultra‐low frequency (ULF) waves. They are observed in particular during quiet times and are indicators of ongoing drift‐resonant processes and resulting radial tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Future work using satellites with coverage of higher latitudes, such as Arase, will provide a better view of the distribution of drift-periodic flux oscillations at a broader range of latitudes and shed light on a deeper understanding of the latitudinal dependence of this phenomenon. Some recent event studies on flux oscillations suggested the potentially important role of local PSD radial gradient (e.g., Hartinger et al, 2020;Sarris et al, 2021;Zhao et al, 2021). Thus, we also explore the role of electron PSD radial gradient using the statistical approach.…”
Section: Statistical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work using satellites with coverage of higher latitudes, such as Arase, will provide a better view of the distribution of drift-periodic flux oscillations at a broader range of latitudes and shed light on a deeper understanding of the latitudinal dependence of this phenomenon. Some recent event studies on flux oscillations suggested the potentially important role of local PSD radial gradient (e.g., Hartinger et al, 2020;Sarris et al, 2021;Zhao et al, 2021). Thus, we also explore the role of electron PSD radial gradient using the statistical approach.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Some recent event studies on flux oscillations suggested the potentially important role of local PSD radial gradient (e.g., Hartinger et al., 2020; Sarris et al., 2021; Zhao et al., 2021). Thus, we also explore the role of electron PSD radial gradient using the statistical approach.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Figure 1 illustrates this process: the particles carry their initial phase-space density with them as they move in L. Drift phase structure arises because the displacement is phase-dependent. The size of the drift phase structure depends on the displacement in L and the local phase space density gradient (for a statistical investigation of this phenomenon, see Sarris et al, 2021). As noted by Hartinger et al (2020) if there is no radial gradient in the phase space density, radial transport will not result in drift phase structures, including drift echoes; this is common in the outer zone at ∼MeV energies.…”
Section: Diffusion Coefficient and Drift Phase Structurementioning
confidence: 98%
“…Drift phase structure arises because the displacement is phase‐dependent. The size of the drift phase structure depends on the displacement in L and the local phase space density gradient (for a statistical investigation of this phenomenon, see Sarris et al., 2021). As noted by Hartinger et al.…”
Section: Estimating the Size Of Drift Phase Structurementioning
confidence: 99%
“…Using a test-particle simulation, they showed that such energy-dependent flux oscillations can be well explained by the resonant interactions caused by m = 1 broadband ULF waves. In addition, Sarris et al (2020Sarris et al ( , 2021 showed that the amplitude of such flux oscillations is well correlated with the particle detector's energy channel width and the radial gradient of electron PSD.…”
mentioning
confidence: 99%